Monitoring Changes in Groundwater Resources Due to Increased Surface Water Delivery Efficiencies in the Lower Republican River Basin - Brookfield, Andrea; Layzell, Anthony; Zhou, Tingxuan; Tian, Boyao (Midcontinent Geoscience, 2023)
Groundwater and surface water, including such engineered surface water bodies as irrigation canals and drainage ditches, are connected. As such, changes to the management of these surface water bodies will affect interconnected groundwater systems as well. In the Lower Republican River Basin in Kansas, United States, a regional irrigation district has converted several irrigation canals to buried pipe to reduce water lost to evapotranspiration and groundwater recharge, increasing the delivery efficiency of its system. The objective of this work was to investigate the change in local groundwater levels due to this conversion. Seven existing wells in the vicinity of converted or soon-to-be converted irrigation canals were equipped with pressure transducers, and hourly water-level measurements were collected over several years. Average water levels decreased in all wells post-conversion compared to measurements taken between 1970 and 2001. The water levels did not decrease equally, and in several wells, the water-level variance also changed from pre- to post-conversion. It is hypothesized that the observed changes are controlled by many factors, including those related to canal conversion (proximity to the converted canal and time since canal conversion), proximity to other surface water features such as the main stem of the canal and reservoir, and subsurface characteristics that influence the rate of infiltration from precipitation events. This research highlights the interconnectedness of surface and subsurface water resources and how water management decisions need to consider how these interactions may change to support sustainable water use.